ENO1 promotes PDAC progression by inhibiting CD8+ T cell infiltration through upregulating PD-L1 expression via HIF-1α signaling - Aziguli Tulamaiti; Shu-Yu Xiao; Yan Yang; Musitaba Mutailifu; Xia-Qing Li; Shi-Qi Yin; Hong-Tai Ma; Hong-Fei Yao; Lin-Li Yao; Li-Peng Hu; Jun Li; Shu-Heng Jiang; et al. (Translational Oncology)
Metabolic reprogramming is a hallmark of cancer. The“Warburg effect”, also known as aerobic glycolysis, is an essential part of metabolic reprogramming and a central contributor to cancer progression. Moreover, hypoxia is one of the significant features of pancreatic ductal adenocarcinoma (PDAC). Under hypoxic conditions, the “Warburg effect” occurs to meet the nutrient and energy demands of rapid genome replication, remodeling the tumor microenvironment (TME) and influencing tumor immunity. α-Enolase (ENO1) is a multifunctional protein, acting as a glycolytic enzyme that catalyzes the conversion of 2-phosphoglyceric acid to phosphoenolpyruvic acid. ENO1 was found to be overexpressed in multiple types of cancers. Here, we investigated the role of ENO1 in modulating the PDAC microenvironment.Using bioinformatic analyses, we demonstrated that ENO1 was highly expressed in PDAC patients, which was related to a poor prognosis. In vitro, Eno1 knockdown resulted in reduced PDAC cell proliferation and colony formation, along with enhanced apoptosis in PDAC cells. In vivo, tumorigenesis was suppressed in mouse PDAC models by Eno1 knockdown. Flow cytometry analysis revealed that high expression of Eno1 altered the tumor immune microenvironment (TIME), particularly the impaired tumor infiltration and function of CD8+ T cells. Mechanistic studies revealed that ENO1 upregulated PD-L1 to prevent CD8+ T cells infiltration through the hypoxia-inducible factor (HIF)-1α signaling pathway, leading to PDAC progression.In conclusion, our findings indicate that ENO1 might serve as a potential biomarker for PDAC and a novel onco-immunotherapeutic target via its role in altering the TIME.